2019
DOI: 10.17586/2220-8054-2019-10-6-694-700
|View full text |Cite
|
Sign up to set email alerts
|

Facile combustion synthesis of TbFeO3 nanocrystals with hexagonal and orthorhombic structure

Abstract: In this research, the formation process of nanocrystalline terbium orthoferrite (TbFeO 3) obtained via a solution combustion technique was studied using powder X-ray diffractometry, scanning electron microscopy, 57 Fe Mössbauer spectroscopy, N 2 adsorption analysis, and FTIR spectroscopy. It was shown that glycine-nitrate combustion method permits one to obtain TbFeO 3 of three different modifications: orthorhombic o-TbFeO 3 (Pbnm), hexagonal h-TbFeO 3 (P6 3 /mmc) and amorphous am-TbFeO 3. It was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
0
15
0
3
Order By: Relevance
“…This method provides a higher dispersion and uniformity for the synthesized powders, including stoichiometric composition, which helps to solve the problem of their sinterability, and brings the properties of materials based on them closer to the properties of single-crystal samples. Examples of the structures of highly dispersed Ca Recently, the solution combustion (SCS) method has been used to obtain new nanostructured multiferroic materials with unique magnetic, electrical, and catalytic properties based on rare-earth element (REE) orthoferrites RFeO 3 (R = Y, Ln) [194,207,231,297,[303][304][305][306][307][308][309][310] with a perovskite-like structure, combining ferromagnetic and ferroelectric ordering. In some cases, it has been shown that the use of additional heat treatment of solution combustion products and other chemical precursors leads to the formation of metastable forms of REE orthoferrites and a significant change in the functional characteristics of materials based on them [231,311,312].…”
Section: Features Of the Implementation Of The Combustion Methods Of Gel-like Media In High-speed Kinetic Modementioning
confidence: 99%
“…This method provides a higher dispersion and uniformity for the synthesized powders, including stoichiometric composition, which helps to solve the problem of their sinterability, and brings the properties of materials based on them closer to the properties of single-crystal samples. Examples of the structures of highly dispersed Ca Recently, the solution combustion (SCS) method has been used to obtain new nanostructured multiferroic materials with unique magnetic, electrical, and catalytic properties based on rare-earth element (REE) orthoferrites RFeO 3 (R = Y, Ln) [194,207,231,297,[303][304][305][306][307][308][309][310] with a perovskite-like structure, combining ferromagnetic and ferroelectric ordering. In some cases, it has been shown that the use of additional heat treatment of solution combustion products and other chemical precursors leads to the formation of metastable forms of REE orthoferrites and a significant change in the functional characteristics of materials based on them [231,311,312].…”
Section: Features Of the Implementation Of The Combustion Methods Of Gel-like Media In High-speed Kinetic Modementioning
confidence: 99%
“…For the application of this class of compounds in these areas, structural parameters are especially important, among which the size of particles and their size distribution should be singled out separately [14]. In recent years, a large number of methods have been used to obtain ferrite nanopowders of various compositions, including hydrothermal synthesis [15], co-precipitation method [16], solution combustion method [17], sol-gel synthesis [18], and many other methods. Each of these types of synthesis has its advantages and disadvantages, but from the point of view of possible industrial scale-up, various methods of solution combustion are of particular interest [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Ferrites-spinels and orthoferrites of rare earth elements remain relevant objects of research for many decades due to their wide application in many areas of modern science and technology [1][2][3]. In addition to the well-known classical areas of their application, such as the production of hard and soft magnets [4], magnetic fluids [5], sensors [6], microwave devices [7], etc., in recent years, new opportunities have been opening up with the use of nanostructured ferrites as materials with high antibacterial activity [8], MRI contrast agents [9], photocatalysts [10], materials for wastewater treatment [11], magnetically recoverable catalysts [12] and many others.…”
Section: Introductionmentioning
confidence: 99%